Tectonic-fluid evolution of an ultra-deep carbonate reservoir in the southern Halahatang Oilfield area, Tarim Basin, NW China. (November 2022) - Liu, Jiaqing; Li, Zhong; Wang, Xu; Jiang, Lei; Feng, Yunxian; Wallace, Malcolm W.
Abstract: Several giant oilfileds have been discovered during recent exploration in the Ordovician carbonates in zone between the Awati and Manjiaer depressions, Tarim Basin, China. These oilfields are deeply buried (>7000 m), and most productive wells are found adjacent to fault zones, suggesting faults may play a crucial role in reservoir development. Here, we use petrographic, microanalytical and geochemical techniques on different stages of void-filling calcite cements to decipher the tectonic-fluid evolution history. Vugs are generally occluded by V1 and V2 calcite cements, which precipitated from marine and burial diagenetic fluids. Two major episodes of fluid invasion are evident in each set of fractures from Middle Ordovician strike-slip faults (F1) to Late Devonian to the Permian strike-slip faults (F2). The sub-horizontal fracture-filling F1 calcite cements show the involvement of near-surface marine to marine-evolved brines, given that δ 18 Ocarb, restored δ 18 Ow values and rare earth element and yttrium (REY) profiles of F1-1 calcite cements are comparable to Ordovician seawater. The F1-2 calcite cements are characterized by negative δ 18 Ocarb, positive restored δ 18 Ow, and apparent Ce positive anomalies. The sub-vertical fracture-filling ferroan F2-1 calcite cements with fluorescence show the highest restored T (Δ47 ) (up to 125 °C), high restored δ 18 Ow values (up to +7.0‰ VSMOW), and an enrichment in MREE, which is consistent with an origin from hot hydrocarbon-bearing basinal brines. The subsequent F2-2 calcite cements may have precipitated during the Late Permian from mixing of basinal brines and deeply circulated meteoric water, as suggested by significantly negative δ 18 Ocarb values, cooler restored T (Δ47 ), negative restored δ 18 Ow values (down to −5.9‰ VSMOW), and flat REY patterns. The 87 Sr/ 86 Sr ratios of calcite cements are similar to coeval seawater. This study highlights the importance of fault-related fluid circulation in the development of a hydrocarbon reservoir, and may be applicable to other deep carbonate-hosted reservoirs. Highlights: Acidic fluids associated with several stages of hydrocarbon emplacement are an important corrosive agent during the burial. Deeply circulated meteoric water during Late Permian facilitated further dissolution. Hydrocarbon-bearing fluids and strike-slip faults are critical factors governing the distribution of the reservoirs. The measured clumped isotope temperatures are higher than the original precipitation temperatures.